Developing a Nudge Process Model for Marketing in SME Contexts: Case Smartmile - Kaaja, Kati (My University, 2019)
Today’s marketer must adjust to constant change creatively. Nudging offers unique potential to develop new ways of influencing consumer behavior. Nudges work by altering the decision environment, steering people towards the most beneficial outcomes for themselves and for others. Despite the blooming popularity of nudges, nudging is still finding its way into marketing concepts and establishing its position in the academic world. This study aims at taking a step forward in conceptualizing nudge marketing through action research, by forming a nudge process model that can be used as a tool when designing market nudges. The nudge process model is formed by looking into the conceptualizations of nudge theory, comparing existing nudge process models, and adding a marketing perspective. A case is brought along to experiment the model in real-life marketing actions of an SME (small and medium-sized enterprises) to find out what kind of potential nudging really has in the field of marketing. The nudge process model formed includes five steps: (1) defining goals, (2) mapping the context, (3) designing the nudge, (4) testing, and (5) evaluation. Secondary steps and helping questions are added to the process after experimentation to make the application of the model in real-life contexts as simple and quick as possible. The nudge process model formed is tested by forming a set of nudges and experimenting them in a real-life context on four social media channels of the case company; Facebook, Instagram, Twitter and LinkedIn. The objectives of the experimentation are to increase engagement on social media posts promoting sustainability on different scales. The nudges experimented are pro-social, transparent nudges that influence the cognitive system of thinking. The nudge tool used is ‘uses of social norms’. The findings of the study confirm that the nudge process model formed is functional in a real-life environment in an SME’s marketing actions. The model is created to be flexible, thus researchers and practitioners across fields may apply the process in their projects. The results of testing a set of nudges support the varying results of nudge theory implications. The nudges were best received on the Finnish Facebook page of the case company, and the most unsuccessful the posts were on Twitter. This may suggest that Facebook users react generally positively on nudges, whereas Twitter users are more reserved when it comes to nudging. Confirming these conclusions would require more research. Forming a nudge process model applicable in real-life marketing actions enables further testing for market nudges and thus, takes a step forward in establishing nudge marketing in the academic world.
Keywords: Nudging; Nudge Marketing; SME; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|